Gelsemine inhibits proliferation and invasion of rheumatoid arthritis synovial fibroblast through down-regulating circ_001680 - LIU Xin-bing, ZHANG Mei-hong (Jichu yixue yu linchuang, 2022)
Objective To investigate the effect of gelsemine on the proliferation, migration and invasion of rheumatoid arthritis endothelial cells (RASFs) and its possible mechanism. Methods RASFs were isolated and cultured. After RASFs were intervened with 50, 100, 200 μg/mL gelsemine for 24 h or small interfering RNA or over-expression vector of circular RNA circ_001680 was transfected into RASFs, cell proliferation was measured by CCK-8 method and clone formation test, cell migration was detected by scratch test, cell invasion was examined by Transwell, the protein expression of E-cadherin and N-cadherin was detected by Western blot. The protein expression of circ_001680 was examined by RT-qPCR. Results Gelsemine or interference with circ_001680 expression reduced the A value, the number of clones, the healing rate of scratches and the number of invaded cells of RASFs and the protein expression of N-cadherin in cells (P＜0.05), and promoted the protein expression of E-cadherin (P＜0.05). Gelsemine reduced the expression of circ_001680 in RASFs (P＜0.05), and the over-expression of circ_001680 reduced the inhibitory effect of gelsemine on the proliferation, migration and invasion of RASFs. Conclusions Gelsemine may inhibit the proliferation, migration and invasion of RASFs, and its mechanism is potentially related to the down-regulation of circ_001680 expression.